2016
DOI: 10.1093/jcr/ucw044
|View full text |Cite
|
Sign up to set email alerts
|

Is Eco-Friendly Unmanly? The Green-Feminine Stereotype and Its Effect on Sustainable Consumption

Abstract: Why are men less likely than women to embrace environmentally friendly products and behaviors? Whereas prior research attributes this gender gap in sustainable consumption to personality differences between the sexes, we propose that it may also partially stem from a prevalent association between green behavior and femininity, and a corresponding stereotype (held by both men and women) that green consumers are more feminine. Building on prior findings that men tend to be more concerned than women with gender-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
387
6
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 493 publications
(434 citation statements)
references
References 66 publications
28
387
6
13
Order By: Relevance
“…However, contrary to expectation, hypothesis 5a and 6a were not supported. These results are somewhat different from those of other studies [18,[93][94][95], which suggested that females are more sensitive to green behavior. This study showed that there is no gender gap in the relationship between (1) overall image and word-of-mouth intentions and (2) overall image and willingness to pay more in an environmentally friendly airline context.…”
Section: Theoretical Implicationscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, contrary to expectation, hypothesis 5a and 6a were not supported. These results are somewhat different from those of other studies [18,[93][94][95], which suggested that females are more sensitive to green behavior. This study showed that there is no gender gap in the relationship between (1) overall image and word-of-mouth intentions and (2) overall image and willingness to pay more in an environmentally friendly airline context.…”
Section: Theoretical Implicationscontrasting
confidence: 99%
“…Han et al [18] also showed that if the hotel has an eco-friendly image, female customers are more likely to (1) stay at the hotel; (2) say positive things about the hotel to others; and (3) pay more for the hotel. Brough et al [93] investigated the gender gap in sustainable consumption using 472 samples. They suggested that the green-feminine stereotype plays an important in the formation of sustainable consumption.…”
Section: The Moderating Role Of Gendermentioning
confidence: 99%
“…This is consistent with previous studies finding that females are more concerned about the environment than are males (Cottrell, 2003;Dietz, Kalof, & Stern, 2002;Hunter et al, 2004). Brough et al (2016) summarize a number of reasons for this. Bearing in mind the absence of this subtle gender difference among visitors, we hypothesize that male residents of this relatively non-urbanized small island and relatively traditional society tend to assume more responsibility in family livelihood than do females and therefore show less approval toward some pro-environmental notions.…”
Section: Discussionsupporting
confidence: 92%
“…Brough et al [79] conducted a research study in green-feminine stereotype and suggested that "this green-feminine stereotype may motivate men to avoid green behaviors in order to preserve a macho image" (p. 567). Stewart [21] argued that the conclusion might not be applicable to sustainable apparel consumption because the statistics from an eco-focused outdoor brand shows that there are about equal numbers of men and women who purchase its eco-friendly apparel.…”
Section: Discussionmentioning
confidence: 99%